China's quest for innovation: Progress and bottlenecks - Alicia García Herrero; Robin Schindowski (Bruegel, 2023)
As the Chinese economy continues to decelerate, the central government is investing heavily in innovation, doubling down on research and development (R&D) spending and STEM-oriented human capital. In this paper, we assess China's progress so far, looking at the inputs to innovation (R&D and human capital) as well as intermediate targets, such as scientific research and patents. We then evaluate how China has fared with respect to the ultimate goal of commercialising this progress, by looking at the value-added of Chinese exports and the overall productivity of the economy. We identify three potential bottlenecks that might be hindering the translation of China's innovation efforts into productivity growth.
Keywords: 330; EU-China relations; growth; Covid-19; industrial policy